2018
DOI: 10.1088/1748-9326/aab326
|View full text |Cite
|
Sign up to set email alerts
|

Uniform shrub growth response to June temperature across the North Slope of Alaska

Abstract: The expansion of woody shrubs in arctic tundra alters many aspects of high-latitude ecosystems, including carbon cycling and wildlife habitat. Dendroecology, the study of annual growth increments in woody plants, has shown promise in revealing how climate and environmental conditions interact with shrub growth to affect these key ecosystem properties. However, a predictive understanding of how shrub growth response to climate varies across the heterogeneous landscape remains elusive. Here we use individual-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 43 publications
4
16
0
Order By: Relevance
“…In this harsh environment for woody plants growth, we found one weather variable—summer temperature—to stand out as main driver of both the vascular plant community's above‐ground biomass and S. polaris below‐ground ring growth. This is in line with previous findings across arctic and alpine shrubs (Ackerman et al, ; Buchwal et al, ; Elmendorf et al, ; Forbes et al, ; Myers‐Smith, Elmendorf, et al, ; Van der Wal & Stien, ; Weijers et al, ). Sun exposure has also been suggested to potentially influence S. polaris ring growth on Svalbard (Owczarek & Opała, ), and that of the net above‐ground production of tundra vascular plants in general (Muraoka et al, ; Van der Wal & Hessen, ; Wiegolaski, Bliss, Svoboda, & Doyle, ).…”
Section: Discussionsupporting
confidence: 91%
“…In this harsh environment for woody plants growth, we found one weather variable—summer temperature—to stand out as main driver of both the vascular plant community's above‐ground biomass and S. polaris below‐ground ring growth. This is in line with previous findings across arctic and alpine shrubs (Ackerman et al, ; Buchwal et al, ; Elmendorf et al, ; Forbes et al, ; Myers‐Smith, Elmendorf, et al, ; Van der Wal & Stien, ; Weijers et al, ). Sun exposure has also been suggested to potentially influence S. polaris ring growth on Svalbard (Owczarek & Opała, ), and that of the net above‐ground production of tundra vascular plants in general (Muraoka et al, ; Van der Wal & Hessen, ; Wiegolaski, Bliss, Svoboda, & Doyle, ).…”
Section: Discussionsupporting
confidence: 91%
“…Moisture may become more limiting at these warmer temperatures. Ackerman et al (2018) found evidence of temperature-induced moisture limitation during warm years in Salix pulchra consistent among four different landscapes in arctic Alaska. In a relatively dry climate of western Greenland, Gamm et al (2017) found declining growth of deciduous shrubs related to increasing moisture limitation in a warming climate.…”
Section: Discussionmentioning
confidence: 62%
“…Most arctic tundra studies have found maximum NDVI to be positively correlated with summer temperature across the circumpolar arctic (Raynolds et al 2008;Bhatt et al 2017), North America , and arctic Alaska Verbyla 2008). Field studies have also shown a strong positive relationship between shrub ring growth and summer temperature in willow (Salix pulchra; Ackerman et al 2018) and dwarf birch (Betula nana; Blok et al 2011a;Li et al 2016). Summer temperature may be the most influential factor controlling variation in arctic shrub growth (Myers-Smith et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations